The Image Politics of Puan Maharani in the Podcast ROSI - Laili, Nisful; Pawito, Pawito; Hastjarjo, Sri (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2024)
Podcasts are typically employed by political figures to attract public attention and build a political image. Puan Maharani, a chair of the House of Representatives, who has a bad image in society, uses this media to build a positive image with clarification content. This research aims to analyze the podcast ROSI by KompasTV with a guest Puan Maharani, allegedly intended to build a positive image. This is qualitative research with Fairclaugh analysis at three levels, micro, meso, and macro. At the micro level, we found representations of the texts delivered by Puan Maharani; at the meso level, we found that the existing representations were discourses to build her political image; and at the macro level, we revealed a deep understanding of the use of podcasts for creating and improving a positive political image. Puan's clarification was conveyed well in the podcast. Apart from that, regarding the issue of Megawati’s interference in Puan's position as the Indonesian House of Representatives, Puan clarified no interference at all.